Implementasi Algoritma RC4 pada Sistem Pengamanan Dokumen Digital Soal Ujian - Fauziyah Suwarsita Febriyani; Arief Arfriandi (JISKA (Jurnal Informatika Sunan Kalijaga), 2021)
The development of science and technology has led to changes in the use of documents in life to become digital data. However, this can cause problems, namely regarding data security and confidentiality. To increase security and confidentiality can be done with cryptographic algorithm RC4. The research method uses the Waterfall method. The result of this research is a website that can secure document files with * doc extension using the RC4 algorithm. The test was carried out using the blackbox test and the CrackStation test for encryption testing. The results of the test show that the website can run well and successfully implements the RC4 algorithm.